Learning of connective tissue by macroscopic dissection of chicken wing - Kawabata, Ryuji (Structure and Function, 2019)
The subject of learning the structure and function of a normal human body is an important and essential study for those aiming for a medical profession (para-medical). The human body consists of enormous cells and body fluids and stroma. By mixing them in various proportions, tissues, organs, and organ systems are created. Thus, the human body can be subdivided into individual layers. The tissues constituting the human body are roughly divided into four. That is, epithelial tissue, connective tissue (supporting tissue), muscle tissue, nerve tissue. Among them, connective tissue has been traditionally known to have various descriptions in classification methods, terms, and locations depending on textbooks, and due to poor specimens and models, etc., the connective tissue is a concept that is hard to understand for the student. To understand such anatomical terms, it is useful to dissect the living organism and observe it directly. Although animal dissection is a highly educational effort, it is avoided due to various circumstances. In this paper, the author proposes dissection of chicken wing as a method to promote understanding of connective tissue. By dissection of wings, more than half of the main connective tissue types can be observed. It is also effective to be able to feel connective tissue strongly or loosely connected between tissues through dissection and anatomic working. Therefore, chicken wings are very good biological materials for understanding the connective tissue.